Extraction of volatile oil from Cymbopogon citratus / Nor Zur Ain Zakaria - Zakaria, Nor Zur Ain (Faculty Of Applied Sciences, 2017)
Cymbopogon citratus commonly known as lemongrass which widely used over many years for several purposes such as in medicine, cooking fragrance, aromatherapy and many more. This study aimed to evaluate the extraction of essential oil from fresh. rhizome and leaves of C. citratus and its chemical composition with the different solvent used (hexane and dicholoromethane). The essential oil was obtained by hydrodistillation process followed by solvent extraction and rotary evaporator. The bioactive compounds of C. citratus have been tentatively analyzed with the aid of gas chromatographymass spectrometry (GC-MS). Different part of lemongrass used gives the different amount of essential content. Rhizome part of C. citratus showed the significant effect in its essential oil content and revealed the higher presence of chemical compound compared to leaves. Analysis of oil revealed the presence of ten compounds in leaves and fourteen compounds in rhizome respectively with different solvent Dicholoromethane showed the marked effect on the proportion of the various components compared to hexane. (ὰ citral was found to be the major compound in leaves part with the percent of similarity index (76.2% and 75.3%), whereas C. citratus rhizome obtained epoxy-linalooloxide as its major compound (81.1% and 82.6%) even the different solvent used in its extraction (dicholoromethane and hexane).